Capital structure determinants of Non-Bank Financial Institutions (NBFIs) in Bangladesh - Siddiqui, Sayla Sowat (© 2012 World Review of Business Research, 2016)
This article was published in World Review of Business Research [© 2012 World Review of Business Research] and the definite version is available at: http://www.wrbrpapers.com/static/documents/January/2012/5.%20Sayla.pdf The article website is at: http://www.wrbrpapers.com/previous_issue/January/2012